IoT-based Smart Garbage Monitoring - Siti Sarah Md Ilyas (Journal of Computing Research and Innovation, 2021)
Smart Garbage Monitoring System using Arduino and Blynk is an IoT-based project that is integrated with cloud computing service. It was developed specifically to help janitors and residential college representative committee in a public university in Malaysia in monitoring the level of garbage in the dustbin through Blynk application, which makes it easy to empty the dustbin and optimize the garbage collection time. This project uses ultrasonic sensor to measure the level of garbage in the dustbin and the data can be viewed through mobile application, Blynk. It will also notify users through email once the garbage bin capacity is full. Other than notification function, Smart Garbage Monitoring System also consists of automatic open and close lid, track dustbin location and humidity level. The objectives of this project are to design the IoT system that detects the level of the garbage displayed in Blynk and an LCD attached to the dustbin and to validate the user acceptance test for the system. The development of Smart Garbage Monitoring System used the System Development Life Cycle (SDLC) by implementing the agile model as the methodology. A User Acceptance Testing was conducted with 20 respondents including students from the student representatives’ body and janitors. This testing aimed to determine the acceptance of the system by conducting an evaluation. The results of the User Acceptance Test shows that most of the participants agreed and verified that the system works for them and a suitable solution for their problems. Therefore, based on the features and functionalities offered by the Smart Garbage Monitoring System, it could be concluded that this system is beneficial to all the users, especially the janitors and students of the residential college.